Identification of thermo optical parameters in 4-hexyloxy-4-cyanobyphenyl with dispersed ZnO nano particles. - Pardhasaradhi, Pokkunuri; Taraka Phani Madhav, Boddapati; Srilekha, Gandu; Ramakrishna Nanchara Rao, Manepalli; Venkata Ganesh, Gorla (Zeitschrift für Naturforschung Section A: A Journal of Physical Sciences, 2021)
In this present article, synthesis, characterization, and study of optical parameters through image enhancement methods have been carried out on 4-hexyloxy-4-cyanobyphenyl (6OCB) pure liquid crystal (LC) and 6OCB with dispersion of 0.5 wt% ZnO nanoparticles. Textural determinations of the synthesized compounds are recorded by using SDTECHS POM connected with a hot stage and camera. differential scanning calorimetry (DSC) is used to measure enthalpy and transition temperature values. The results show that the dispersion of ZnO in 6OCB exhibits nematic phase as same as the pure 6OCB with slightly reduced clearing temperature as expected. Further characterization is carried out by various spectroscopic techniques like X-ray diffraction (XRD), scanning electron microscopy (SEM), and ultraviolet visible (UV–Vis) spectroscopy. To evaluate and identify the behavior of optical parameters viz optical transmittance (OT), absorption coefficient (AC), and phase retardation (PR) as a function of temperature, an image processing method has been proposed, i.e. illumination enhancement algorithm (IEA) using MATLAB software. The proposed enhancement algorithm is one of the simplest and efficient algorithms to evaluate the thermo optical parameters for various electro optical applications. The results are compared with the body of the data available.